Non‐clinical safety evaluation of repeated intramuscular administration of the AS15 immunostimulant combined with various antigens in rabbits and cynomolgus monkeys. Issue 2 (1st June 2015) - Garçon, N.; Silvano, J.; Kuper, C. F.; Baudson, N.; Gérard, C.; Forster, R.; Segal, L.
Abstract: Combination of tumor antigens with immunostimulants is a promising approach in cancer immunotherapy. We assessed animal model toxicity of AS15 combined with various tumor antigens: WT1 (rabbits), or p501, dHER2 and recPRAME (cynomolgus monkeys), administered in seven or 20 dose regimens versus a saline control. Clinical and ophthalmological examinations, followed by extensive post‐mortem pathological examinations, were performed on all animals. Blood hematology and biochemistry parameters were also assessed. Antigen‐specific antibody titers were determined by enzyme‐linked immunosorbent assay. Additional assessments in monkeys included electrocardiography and immunohistochemical evaluations of the p501 expression pattern. Transient increases in body temperature were observed 4 h or 24 h after injections of recPRAME + AS15 and dHER2 + AS15. Edema and erythema were observed up to 1 week after most injections of recPRAME + AS15 and all injections of dHER2 + AS15. No treatment‐related effects were observed for electrocardiography parameters. Mean fibrinogen levels were significantly higher in all treated groups compared to controls, but no differences could be observed at the end of the treatment‐free period. Transient but significant differences in biochemistry parameters were observed post‐injection: lower albumin/globulin ratios (p501 + AS15), and higher bilirubin, urea and creatinine (dHER2 + AS15). Pathology examinations revealed significant increases in axillary lymph node mean weights (recPRAME + AS15) compared to controls. A 100% seroconversion rate was observed in all treated groups, but not in controls. p501 protein expression was observed in prostates of all monkeys from studies assessing p501 + AS15. These results suggest a favorable safety profile of the AS15‐containing candidate vaccines, supporting the use of AS15 for clinical development of potential anticancer vaccines. Copyright © 2015 The Authors. Journal of Applied Toxicology Published by John Wiley & Sons Ltd. Abstract : The aim of the current paper was to assess the safety profile of vaccine candidates containing the AS15 immunostimulant combined with different antigens in two animal models. Several antigens were tested for this purpose: WT1 (rabbits), p501, dHER2 and recPRAME (cynomolgus monkeys). Only transient differences in hematology and biochemical parameters could be observed, while pathology testing revealed no safety concerns. Our findings support the use of AS15 for clinical development of potential immunotherapeutic cancer vaccines.